Application prospects of cerebrospinal fluid DIA techniques in identifying key regulatory molecules for mental disorders in encephalitis. Issue 1 (28th March 2021) - Zhou, Lin; Wang, Zheng‐Meng; Wen, Song; Li, Juan; Xiong, Liu‐Lin; Zhu, Zhao‐Qiong
Abstract : At present, data independent acquisition (DIA) protein spectrum detection technology is one of the most attractive mass spectrometry acquisition techniques, which once led the new development of quantitative proteomics. Its application fields include the screening of clinical disease markers, the study of action mechanism, the study of drug targets and so on. DIA has been wide‐ranging used in clinic because of its high throughput, high resolution and high reproducibility. The occurrence of mental disorders in encephalitis is common, and such neurocognitive impairment has a dramatically impact on the disease progression and prognosis of patients, which undoubtedly increases the economic burden of sufferers' families and society. Under the circumstance that the mechanism of mental disorder of encephalitis is still unknown, this paper summarizes a large number of literatures of encephalitis, originates the possibility of the application of cerebrospinal fluid detection by DIA in the occurrence of mental disorder of encephalitis, seeks for biomarkers for the occurrence of mental disorder of encephalitis, and provides clinical guidance.